Proximate Composition, Phenolic Content, and Antioxidant Activity of the pulp and pericarp of Takob Akob Fruit (Garcinia parvifolia) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Takob Akob (Garcinia parvifolia) is a lesser-explored indigenous fruit from Sabah, Malaysia, known for its sour taste, which limits its use in daily nutrition and commercialization. This study aims to determine the proximate composition, phytochemical content, and antioxidant activity of the fruit to enhance knowledge of its nutritional benefits. The pulp and pericarp were analysed using AOAC 2000 methods, while phytochemical content and antioxidant activity were assessed using a spectrophotometer. Results showed that the pulp had higher fat (12.61±0.16%) and protein (4.14±0.12%) content than the pericarp (fat: 8.78±0.47%, protein: 2.67±0.04%). However, carbohydrate content was greater in the pericarp (41.80±0.43%) than in the pulp (37.19±0.49%). Phytochemical analysis revealed higher phenolic (0.22±0.01 mg GAE/g), flavonoid (1.32±0.02 mg QE/g), and antioxidant activity in the pulp compared to the pericarp, whereas carotenoid content was higher in the pericarp (58.35±0.33 μg/g) than in the pulp (22.85±0.34 μg/g). Antioxidant activity, measured using DPPH and ABTS methods, was also greater in the pulp. These findings suggest that the pulp of Takob Akob contains higher micronutrients, phytochemicals, and antioxidant activity than the pericarp, making it a potential functional food ingredient. Further research is needed to optimize its antioxidant properties through improved storage or formulation with other antioxidant-rich ingredients.
Keywords: Garcinia parvifolia; Antioxidants; Phytochemical content; Pulp; Pericarp